Peningkatan Hasil Belajar PAI Dengan Model True or False Kelas IV UPTD SDN 06 Sungai Kamuyang - Siti Kanolasari; Salmiwati Salmiwati; Rina Mala Putri (Jurnal Pendidikan Tuntas, 2024)
This research is motivated by problems based on the results of daily tests in class IV UPTD SDN 06 Sungai Kamuyang on the material let's recite and study Q.S Al-Hujurat / 49: 13 which is still relatively low, below the KKTP, which is still below the score of 70. The low student learning outcomes according to the author's analysis are influenced by learning methods that do not involve students and seem monotonous. The teacher tends to convey the subject matter by lecturing, then the children read the material themselves Let's Recite and Recite Q.S Al-Hujurat / 49: 13 in the package book and memorize it. Also found when learning students are not focused and noisy in learning and feel bored with the methods used. The learning process carried out has not been able to increase the value of student learning completeness. Using the true or false model in the material Q.S Al-Hujurat / 49;13 will hopefully improve student learning outcomes that are better and easier for the student to understand. This study aims to determine the improvement of PAI learning outcomes of fourth grade students of UPTD SDN 06 Sungai Kamuyang with the true or false model. This study used a Classroom Action Research (PTK) design consisting of four stages, namely planning, action implementation, observation and reflection. The subjects of this study were grade IV students totaling 10 students consisting of 7 male students and 3 female students at UPTD SDN 06 Sungai Kamuyang. The results of this study indicate the application of the True or False model to improve learning outcomes by looking at student learning outcomes in cycle I with an average score of 72 (good) and a percentage of completeness of 60% (good), and cycle II with an average score of 82 (very good) with a percentage of completeness of 90% (very good).